MEDIA APLIKASI COMICA SEBAGAI STRATEGI MENINGKATKAN MINAT BELAJAR MAHASISWA PADA MATA KULIAH PEMBELAJARAN IPA MI/SD - Indriani, Irma (FASHLUNA, 2024)
This study aims to obtain data on the extent to which the increase in student interest in learning after the use of comica application-based learning media in students. The type of research used in this research is the Design & Development (D&D) method with a qualitative approach. This research was conducted at the STIT Sunan Giri Bima Campus. The subjects in this study were third semester PGMI study program students in the 2023/2024 academic year. Techniques in collecting data in this study are direct observation and questionnaires. Observing the object of research during learning takes place to find out the student's response after using comic learning media while giving questionnaires is done to find out student interest after using comic learning media. Then filling out the questionnaire is done after students have completed lectures for one semester with 4 face-to-face sessions using comic learning media. The data analysis technique used in this study is to use narrative analysis to directly examine the problems contained in the data as well as to find out to obtain data on the extent to which the increase in student interest in learning after the use of comica application-based learning media in students during the lecture process. Based on the results of observations in this study, it was found that comica application-based learning media in MI / SD science learning courses can increase interest in learning and based on the results of filling out questionnaires, it shows that the response is very high around 90% of students who agree to use comic media.